AI-Powered Mobile Applications in Hotels: Guest Personalization, Operational Efficiency, and Sustainability - Herath Mudiyanselage, Amila Ishanthi; Jain, Neetu; Kaur , Manpreet (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Hotels are adopting artificial intelligence (AI)-enabled mobile apps to provide more personalized and responsive guest experiences while concurrently working toward greater efficiency and sustainability. To date, hospitality research has highlighted technical feasibility over holistic perspectives of managerial benefit, guest acceptance, and sustainable performance implications. This paper aims to provide greater context on these three areas through a qualitative systematic literature review with thematic synthesis of secondary research. Data sources include peer-reviewed journal articles, industry publications, and publicly available evidence from hotels published within the last five years. Results from thematic analysis revealed three outcome areas with prevalent literature. AI-enabled mobile applications are commonly associated with frictionless guest experiences enabled by digital guest journeys from start to finish. Capabilities include, but are not limited to, guest pre-arrival personalization, mobile check-in/ out, digital keys and smart-room controls, requests and payments, loyalty program integration, and chatbots with AI learning capabilities. Second, there is supporting evidence that AI-enabled mobile applications can drive efficiency through automation of low-level guest interactions, better coordination of response efforts, and quantifiable productivity improvements. Additional impacts on operational efficiency are cited through digital workflows and AI-enabled energy management. Lastly, AI-mobile services can allow for enhanced guest convenience/personalization with fewer resources. Caveats revealed benefits include preparation for implementation such as organizational readiness, change management, employee training, rollout strategy, and responsible data practices. Overall, AI-mobile technology has potential to be a strong value-add and differentiation/sustainability tactic for luxury hotels if used in conjunction with staff.